Haemosporidian infection and co-infection affect host survival and reproduction in wild populations of great tits. Issue 14 (December 2018) - Pigeault, R.; Cozzarolo, C.-S.; Choquet, R.; Strehler, M.; Jenkins, T.; Delhaye, J.; Bovet, L.; Wassef, J.; Glaizot, O.; Christe, P.
Graphical abstract: Highlights: Haemosporidian infection and co-infection strongly impact both reproductive success and survival probability of great tits. Co-infections decrease survival but increase reproductive success of birds. The cost of co-infection on survival is higher than the cost induced by a single infection. Co-infected birds have, however, the highest reproductive success. Abstract: Theoretical studies predict that parasitic infection may impact host longevity and ultimately modify the trade-off between reproduction and survival. Indeed, a host may adjust its energy allocation in current reproduction to balance the negative effects of parasitism on its survival prospects. However, very few empirical studies tested this prediction. Avian haemosporidian parasites provide an excellent opportunity to assess the influence of parasitic infection on both host survival and reproduction. They are represented by three main genera ( Plasmodium, Haemoproteus and Leucocytozoon ) and are highly prevalent in many bird populations. Here we provide the first known long-term field study (12 years) to explore the effects of haemosporidian parasite infection and co-infection on fitness in two populations of great tits ( Parus major ), using a multistate modeling framework. We found that while co-infection decreased survival probability, both infection and co-infection increased reproductive success. This study provides evidence that co-infections can be more virulent than single infections. It also provides support for the life-history theory which predicts that reproductive effort can be adjusted to balance one's fitness when survival prospects are challenged.